Didatizar para popularizar: Um estudo sobre a construção de enunciados de divulgação científica em revistas especializadas - SILVA, Aline Kananda Matias (2024)
The Science Divulgation Discourse (SDD) has the role of presenting scientific knowledge to the general reading public, based on a didactic approach, which does not aim to train specialists, but to bring this knowledge to the population that does not belong to the scientific community. The SDD articulates what to say, how to say it, who to say it to and the purpose of publicizing, popularizing what is produced by scientists and aimed at clarifying problems of different kinds present in society. Disseminating, popularizing is a way of contributing to understanding and finding solutions to problems, so it needs to reach many different readers, especially those who seek answers from magazines specializing in science divulgation (SD). In this sense, our aim is to analyze the process of didacticizing the discourse of science communication in specialized journals. Doing this analysis means looking at the heterogeneity shown in the enunciative forms that are used as strategies to popularize scientific knowledge; it means looking at the place of the reader in the construction of this saying with pedagogical value; as well as observing the way in which the science communicator constructs the mediation between science and lay readers. To this end, we analyzed two magazines: Superinteressante and Questão de Ciência. We selected 6 articles from DC as the corpus of analysis, three for each magazine, published between 2020 and 2021. They are statements related to the Covid-19 pandemic. As a research problem, we have the following questions: How is the process of didacticizing science communication established in specialized journals? What strategies involving the heterogeneity of enunciative forms are mobilized by the disseminator to reach the reading public? How does mediation take place between scientific knowledge and the general public? To build the theoretical framework, we invested in Bakhtin (2011), Bakhtin/Volochínov (2014) on the dialogical conception of language, which believes that all discourse is directed towards another, based on a certain intention; in Authier-Revuz (1998) on the concept of discourse as reformulation, which is constructed by the didacticization of scientific knowledge; in Libâneo (2006) on didactics as a process that seeks to promote teaching and learning. In addition to other authors who help us discuss science communication produced in the journalistic sphere. The results show that science communication seeks to establish strategies to teach scientific knowledge to the general public using linguistic and discursive mechanisms that make it easier to understand the meaning and hermetic language linked to the scientific community, as well as a way of democratizing knowledge.